The analysis of the threat of reusing pet bottles for the storage of drinking water - Manuilov, A; Martynov, A (Annals of Mechnikov's Institute, 2019)
Introduction. According to a sociological survey of about 86% of Kharkiv (Ukraine) residents reuse PET bottles for a drinking water storing. This type of reuse of PET bottles isn't safe and the results of numerous research unequivocally confirm this assertion. The largest hazard of plastic bottles reuse for drinking water storage is biological film on the internally surface of bottle. This biofilm may contain pathogenic microorganisms which can migrate from biofilm to fresh water. Human, who drinking contaminated water, may drink microorganisms in common with this water. It's very dangerous, because the numerous strains of pathogens may migration in water and infect from gastric-bowel tract to the humans. Scientists from National technical university "Kharkiv polytechnic institute" in common with experts from Mechnikov institute of microbiology and immunology explored this problem and devised the apparatus, which can destroy a biofilm on polymer or another surface. Materials & Methods. The tested apparatus was the electrical device consisting of a block with electrodes, an electronic control, a water pump and a sprinkler for spraying the disinfectant. The electrode was made of 925˚ silver (sterling silver). Water for the preparation of a disinfectant was tap water and wasn't treated additionally. The sprinkler for spraying the disinfectant was placed in the neck of the infected bottle. Disinfectant solution was sprayed inside the bottle for 4 seconds. The water pressure was about 1.5 atmospheres. After that, the sprinkler was removed and the disinfectant was drained. A smear for microbiological composition was taken from three parts of the bottle - the neck, the middle part and the bottom. Growth of microorganisms and their detections was fixed by classic microbiological methods. Results & Discussion. In the article the scheme of the most probable and widespread way of infection of PET-bottles by pathogens and the way of minimization of this danger is given. Investigation of the contamination of the inner surface of the bottle by infected dust was carried out. It is determined that contaminated dust can cause a very serious infection contamination of inner surfaces of PET bottles and, subsequently, of water. In laboratory conditions and on the real object, a device for sanitizing surfaces was tested. It is established that the prototype of the device generates a disinfectant that destroys the most of known strains of microorganisms. This disinfectant is not toxic and is not dangerous to humans, the only product of evaporation of this product is water. With this disinfectant, the infection contamination on the inside of the PET bottle was completely eliminated. Thus, the use of a prototype device to minimize the threat of contamination of water consumers from recycled PET bottles is possible and very effective. Conclusions. 1. Potable water storage containers made of PET contain threats, the most serious of which is microbiological. 2. Without conducting regular disinfection or inactivation treatment of PET containers may be potential spreaders of human diseases. 3. The formed biological film cannot be destroyed or inactivated by means and substances that are at home. Potentially dangerous is the use of special, concentrated disinfectants at home. 4. Ions of silver are acknowledged in the world of practice antiseptic. 5. The use of silver ions to inactivate the biological film, while complying with state standards and methods of treatment, is safe and effective, which has been proved by research. 6. The developed method and apparatus are effective against the formed biological film and comply with the current legislation of Ukraine and some other countries, in particular the USA and Canada.